FEATURES OF PLASTIC SURGERY OF THE ANTERIOR WALL OF THE MAXILLARY SINUS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
To date, the problem of traumatic injuries of the middle zone of the face remains extremely relevant. According to the WHO, the number of traumatic injuries is still on the rise. According to statistics, skull fractures and intracranial injuries account for 5.1% of the total number of all registered injuries according to the rates of injuries and poisonings and other accidents among the adult population in 2022. In the structure of total injuries, 1.7% is occupied by injuries of the eye and orbit. Patients with injuries of the midface require inpatient treatment in 85% of cases. Trauma to the bones of the facial skull accounts for up to 40% of the entire list of diseases in patients hospitalized for treatment in the departments of maxillofacial surgery, and accounts for almost 21% of the total number of victims with injuries in hospitals of medical institutions. Thus, the frequency of traumatism of the maxillofacial region, and in particular, the frequency of damage to the zygomatic-orbital complex, both in our country and abroad, does not decrease; on the contrary, there is an increase in the number of patients with this pathology.